Diverse responsiveness of dehydrin genes to abscisic acid and water stress treatments in cucumber F1 cultivar hybrids. Issue 6 (2nd November 2019) - Szegő, Anita; Badics, Eszter; Gubala, Dorottya; Oszlányi, Réka; Oyuntogtokh, Bat-Erdene; Kappel, Noémi; Papp, István; Kiss-Bába, Erzsébet
ABSTRACT: Expression of putative dehydrin (DHN) genes of cucumber ( Cucumis sativus L.) was investigated under water deficit stress and after external abscisic acid (ABA) treatment. Three typically open field cultivated along with four greenhouse grown F1 cultivar hybrids were used in the experiments. 'K' segment specific Western blot was applied to characterise DHN proteins expressed in water deprivation while transcription of selected DHN genes was studied by RT-PCR and RT-qPCR. Water-deficit induced differential accumulation of DHN polypeptides in heat stable protein fractions of leaf samples. Greenhouse cultivated hybrids exhibited more pronounced induction of low molecular weight DHN proteins under this condition. The basal transcript level of the Yn SKn type DHN2 gene in the absence of treatments was lower than that of the SKn type DHN3. DHN2 was highly inducible by water stress and ABA application. Transcription of DHN3 was moderately increased by desiccation in most hybrids, while it was only slightly responsive to ABA in all genotypes. F1 hybrids of the same cultivation type did not form distinct groups according to their transcriptional responses to either treatments. Comparison of the expression patterns at the transcript and protein levels pointed to a possibility of translational and/or post-translational regulation of DHN protein abundance.